PISA TASK: WHAT IS THE WEIGHT OF A WEIGHTLIFTING DISC? - Fitra, Dian; Putri, Ratu Ilma Indra; Susanti, Ely (Journal on Mathematics Education)
One way to improve the quality of mathematics learning in Indonesia, achievement in PISA in particular, is by conducting PISA related researches. This study aims to generate a valid, practical, and having potential effect PISA task using a weight-lifting context. It is design research in which the development process was done by the Tessmers formative evaluation. The data were collected through walkthrough, interviews, documentation, and tests. The test items validation process involved three experts at expert review stage and three students in the one-to-one phase. The validity of the items was checked from its compatibility with the PISA framework regarding content, context, literacy process and level of questions. The practicality was examined from small group test results of the six students. The developed items are practical since students easily understand them and they are easy to use. The potential effects of the developed items were seen based on the capabilities students engaged in during their process of solving the given problem. The developed PISA task capable of generating fundamental mathematical competences, i.e., communication; representation; mathematization; reasoning and arguments; choosing strategies to solve problems; using language and symbolic, formal and technical operations.